De-Europeanisation through Discourse: A Critical Discourse Analysis of AKP's Election Speeches. Issue 1 (2nd January 2016) - Aydın-Düzgit, Senem
Abstract: This article takes issue with the question of whether Turkey has been turning away from Europe in recent years, by adopting a critical constructivist lens to understand how, rather than why, Turkey's presumed distance from the European Union (EU) is taking place. In doing that, it seeks to analyse the ways in which the political–societal transformation of the country as distanced from the EU is enabled by certain discursive practices which in turn contribute to the growing rift between Turkey and the EU. This is mainly conducted through a critical discourse analysis (CDA) of texts produced by former Prime Minister and now President Recep Tayyip Erdoğan on Europe and the EU during key election periods starting with the 12 June 2011 general election.